2004
DOI: 10.1159/000082735
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Agouti-Related Protein in Appetite Regulation in a Species with Continuous Nutrient Delivery

Abstract: Knowledge of specific neurotransmitters as well as the pathways and mechanisms regulating appetite in ruminants that continually graze, such as sheep, is incomplete. Although fundamentally agouti-related protein (AGRP) has a similar function across species to increase food intake, the regulation of AGRP may vary across grazing and intermittent feeders. To investigate the role of orexigenic peptides in the regulation of feed intake, we first extracted messenger RNA from sheep that were fasted for 3 days, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 58 publications
(49 reference statements)
0
28
1
Order By: Relevance
“…Upregulation of AgRP mRNA was observed in chronically underfed ewes Archer et al, 2004 andRelling et al, 2010) or castrate male sheep fasted for 4 days . In addition, dual label immunohistochemistry (for AgRP and c-Fos) indicated that fasting for 3 days increased the number of AgRPpositive neurons and the activation of AgRP neurons in the ARC (percentage of AgRP neurons also expressing c-Fos; Wagner et al, 2004). Gene expression for AgRP was also increased in sheep with a low body condition score compared to sheep with a high body condition score (Archer et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Upregulation of AgRP mRNA was observed in chronically underfed ewes Archer et al, 2004 andRelling et al, 2010) or castrate male sheep fasted for 4 days . In addition, dual label immunohistochemistry (for AgRP and c-Fos) indicated that fasting for 3 days increased the number of AgRPpositive neurons and the activation of AgRP neurons in the ARC (percentage of AgRP neurons also expressing c-Fos; Wagner et al, 2004). Gene expression for AgRP was also increased in sheep with a low body condition score compared to sheep with a high body condition score (Archer et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Agouti-related protein AgRP mRNA Adam et al, 2002;Archer et al, 2002a) and AgRP protein (Wagner et al, 2004) were localized to the ARC nucleus in sheep. Cloning of a partial sequence of AgRP mRNA indicated a high homology with bovine AgRP but the comparison of the human message indicated only about 56% homology for the portion cloned (Wagner et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations